Ultrastructural Analysis of Cell Envelope and Accumulation of Lipid Inclusions in Clinical Mycobacterium tuberculosis Isolates from Sputum, Oxidative Stress, and Iron Deficiency - Vijay, Srinivasan; Hai, Hoang T.; Thu, Do D. A.; Johnson, Errin; Pielach, Anna; Phu, Nguyen H.; Thwaites, Guy E.; Thuong, Nguyen T. T. (Frontiers in Microbiology, 2018)
Introduction: Mycobacteria have several unique cellular characteristics, such as multiple cell envelope layers, elongation at cell poles, asymmetric cell division and accumulation of intracytoplasmic lipid inclusions, which contributes to their survival under stress conditions. However, the understanding of these characteristics in clinical Mycobacterium tuberculosis (M. tuberculosis) isolates and under host stress is limited. We previously reported the influence of host stress on the cell length distribution in a large set of clinical M. tuberculosis isolates (n = 158). Here, we investigate the influence of host stress on the cellular ultrastructure of few clinical M. tuberculosis isolates (n = 8) from that study. The purpose of this study is to further understand the influence of host stress on the cellular adaptations of clinical M. tuberculosis isolates. Methods: We selected few M. tuberculosis isolates (n = 8) for analyzing the cellular ultrastructure ex-vivo in sputum and under in-vitro stress conditions by transmission electron microscopy. The cellular adaptations of M. tuberculosis in sputum were correlated with the ultrastructure of antibiotic sensitive and resistant isolates in liquid culture, under oxidative stress, iron deficiency and exposure to isoniazid. Results: In sputum, M. tuberculosis accumulated intracytoplasmic lipid inclusions. In liquid culture, clinical M. tuberculosis revealed isolate to isolate variation in the extent of intracytoplasmic lipid inclusions, which were absent in the laboratory strain H37Rv. Oxidative stress, iron deficiency and exposure to isoniazid increased the accumulation of lipid inclusions and decreased the thickness of the cell envelope electron transparent layer in M. tuberculosis cells. Furthermore, intracytoplasmic compartments were observed in iron deficient cells. Conclusions: Our ultrastructural analysis has revealed significant influence of host stress on the cellular adaptations in clinical M. tuberculosis isolates. These adaptations may contribute to the survival of M. tuberculosis under host and antibiotic stress conditions. Variation in the cellular adaptations among clinical M. tuberculosis isolates may correlate with their ability to persist in tuberculosis patients during antibiotic treatment. These observations indicate the need for further analyzing these cellular adaptations in a large set of clinical M. tuberculosis isolates. This will help to determine the significance of these cellular adaptations in the tuberculosis treatment.